Bioartificial Articular Cartilage Substitute (BACS): advancing functional tissue engineered medical product - Abdul Rahman, Rozlin; Sha'ban, Munirah; Zulkifly, Ahmad Hafiz (2018)
Articular cartilage has poor repair capacity due to its avascular and aneural properties. To date, there is no definitive treatment that can delay or reverse the degenerative process in cartilage. Therefore this bioartificial articular cartilage substitute is one of the alternatives that employ essential tissue engineering triad, which consist of i) quality cell source i.e. autologous bone marrow mesenchymal stem cells (BMSCs), ii) biomaterial scaffolds i.e. synthetic poly(lactic-co-glycolic)acid (PLGA) [+] natural fibrin and iii) signalling factors (chemical and/or physical stimuli) i.e. selected growth medium. All threecomponents are combined together forming PLGA-based scaffolds and BMSCs to restore damaged joint cartilage. Our implant model demonstrated promising findings with satisfactory structural and functional cartilaginous tissue restoration based on the International Cartilage Repair Society (ICRS) classification and the modified O’Driscoll histological grading scale. This reliable autologous matrix-induced cartilage implantation system uses one’s own cells, therefore the approach can be used to bypass certain social and scientific issues surrounding the conventional tissue or organ transplantation.